Expression of suppressor of cytokine signalling 3 (SOCS3) in human bladder epithelial cells infected with uropathogenic Escherichia coli. Issue 2 (25th July 2012) - Demirel, Isak; Säve, Susanne; Kruse, Robert; Persson, Katarina
<x xml:space="preserve">Abstract</x> Suppressor of cytokine signalling (SOCS) proteins inhibit pro‐inflammatory signalling mediated by Janus‐activated kinase (JAK)‐signal transducer and activator of transcription (STAT) pathways. To evade the immune response some pathogens appear to modify the host SOCS proteins. Uropathogenic Escherichia coli (UPEC) are able to subvert the host response evoked by bladder epithelial cells, but the mechanisms are not fully understood. The objective of this study was to investigate whether UPEC can modify the host SOCS and STAT3 response. Real time RT‐PCR studies demonstrated an increased SOCS1 and SOCS3 expression in the isolated human bladder epithelial cell lines (RT‐4 and 5637) in response to cytokines. UPEC strain IA2 increased SOCS3, but not SOCS1, mRNA levels with a peak at 6 h after infection. The increase of SOCS3 was confirmed at the protein level by Western blotting. The UPEC strain IA2 caused a time‐dependent decrease in the phosphorylation of STAT3. This study demonstrates that UPEC are able to affect SOCS3 and STAT3 signalling in human uroepithelial cells. The finding that UPEC are able to induce mediators involved in suppression of host cytokine signalling may help to elucidate how UPEC may circumvent the host response during urinary tract infection.